The impact of technology diffusion in health care markets: Evidence from heart attack treatment - Corinna Hentschker; Ansgar Wübker (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
Medical technological progress has been shown to be the main driver of health care costs. A key policy question is whether new treatment options are worth the additional costs. In this paper we assess the causal effect of percutaneous transluminal coronary angioplasty (PTCA), a major new heart attack treatment, on mortality. We use a full sample of administrative hospital data from Germany for the years 2005 to 2007. To account for non-random treatment assignment of PTCA, instrumental variable approaches are implemented that aim to randomize patients to different likelihoods of getting PTCA independent of heart attack severity. Instruments include differential distances to PTCA hospitals and regional PTCA rates. Our results suggest a 4.5 percentage point mortality reduction for patients who have access to this new treatment compared to patients receiving only conservative treatment. We relate mortality reduction to the additional costs for this treatment and conclude that this new treatment option is cost-effective in lowering mortality for AMI patients at reasonable cost-effectiveness thresholds. – – Medizinisch-technischer Fortschritt ist einer der Hauptgründe für die steigenden Ausgaben im Gesundheitswesen. Daher ist es eine grundlegende Frage, ob neue und teurere Behandlungsmethoden auch den entsprechenden Zusatznutzen erbringen. In dem vorliegenden Artikel bestimmen wir den kausalen Effekt der perkutanen transluminalen Koronarangioplastie (PTCA) auf die Mortalität für Herzinfarktbehandlungen. Wir nutzen administrative Krankenhausdaten aus Deutschland für die Jahre 2005 bis 2007. Da häufig jüngere und gesündere Herzinfarktpatienten die PTCA-Behandlung erhalten und wir nicht für alle Patientencharakteristika kontrollieren können, führen wir eine Instrumentenvariablenschätzung durch, um den kausalen Effekt der PTCA auf die Mortalität zu erhalten. Als Instrument nutzen wir die Zeitdifferenz zu den nächstgelegenen Krankenhäusern. Die Ergebnisse zeigen, dass Patienten, die eine PTCA erhalten eine um 4,5 Prozentpunkte verringerte Mortalität aufweisen als Patienten mit einer konservativen Behandlung. Die zusätzlichen Behandlungskosten der PTCA im Vergleich zum Nutzen der Behandlung lässt die Schlussfolgerung zu, dass PTCA auch eine kosteneffektive Behandlung darstellt.
Keywords: I11; I12; I18; 330; acute myocardial infarction; instrumental variables; mortality